Construction of Sb2Se3 nanocrystals on Cu2−xSe@C nanosheets for high performance lithium storage. (21st August 2019) - Yue, Hailong; Tian, Qi; Wang, Guangming; Jin, Rencheng; Wang, Qingyao; Gao, Shanmin
Abstract : Cu2− x Se@C@Sb2 Se3 with enhanced electrochemical performance was designed and fabricated, where Sb2 Se3 nanoparticles were anchored on Cu2− x Se@C nanosheets. Abstract : Copper selenide as an anode for lithium-ion batteries suffers from volume expansion/contraction, while constructing nanostructured copper selenide with other components is considered as an effective strategy. In this work, Cu2− x Se@C@Sb2 Se3 nanosheets were fabricated through a two step solvothermal procedure with the assistance of glucose. Such a structure can facilitate the migration rate of Li +, enhance the electrical conductivity, buffer the volume variation and prohibit the aggregation of the electrode. As a result, Cu2− x Se@C@Sb2 Se3 exhibits good electrochemical performance with a specific capacity of 341 mA h g −1 after 100 cycles at a current density of 100 mA g −1 and 153 mA h g −1 at a rate of 2000 mA g −1 . Such a structural design and synthetic strategy may also be applied to explore other nanocomposites to improve the electrochemical performance.